LOOP MIGRATION LENGTHENS TRAVEL DISTANCE AND INCREASES POTENTIAL RISKS FOR A CENTRAL ASIAN, LONG-DISTANCE, TRANS-EQUATORIAL MIGRANT, THE RED-FOOTED FALCON - Katzner, T.E.; Bragin, E.A.; Bragin, A.E.; McGrady, M.; Miller, T.A.; Bildstein, K.L. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
Geolocator, ringing and observational data together demonstrate that Red-footed Falcons from northern Kazakhstan have a clockwise loop migration that begins with a long and unusual westward trek around eastern Europe’s large inland seas before continuing to extreme southern Africa. Return migration is farther west and requires crossing two major migratory barriers: the Sahara and the Mediterranean. The loop migration we describe requires an extensive longitudinal movement, exposes central Asian Red-footed Falcons to multiple desert, mountain and marine crossings, and, at outbound and return Mediterranean bottlenecks, crosses sites where raptor shooting is common.
Keywords: Red-footed Falcon; geolocator; Kazakhstan; loop migration